2012
DOI: 10.1007/s00401-012-1044-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathologically defined subtypes of Alzheimer’s disease differ significantly from neurofibrillary tangle-predominant dementia

Abstract: Alzheimer’s disease (AD) can be classified based on the relative density of neurofibrillary tangles (NFTs) in the hippocampus and association cortices into three subtypes: typical AD, hippocampal-sparing AD (HpSp AD), and limbic-predominant AD (LP AD). AD subtypes not only have pathologic, but also demographic, clinical, and genetic differences. Neurofibrillary tangle-predominant dementia (NFTD), a disorder with NFTs relatively restricted to limbic structures, shares this feature with LP AD raising the possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
114
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 42 publications
13
114
0
2
Order By: Relevance
“…Although the disease progression has been traditionally assessed under the Braak and Braak staging scheme (Braak & Braak, 1991), several reports (Akatsu et al., 2002; Armstrong, Nochlin, & Bird, 2000; Janocko et al., 2012; Murray et al., 2014) have demonstrated a very variable AD clinical picture: Neither the progression patterns nor the same anatomical areas are involved or follow a reproducible anatomic sequence, even in series of patients belonging to comparable social and cultural environments. Approximately 25% of AD brains show atypical patterns of structural damage, usually classified as hippocampal sparing and limbic predominant AD (Murray et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the disease progression has been traditionally assessed under the Braak and Braak staging scheme (Braak & Braak, 1991), several reports (Akatsu et al., 2002; Armstrong, Nochlin, & Bird, 2000; Janocko et al., 2012; Murray et al., 2014) have demonstrated a very variable AD clinical picture: Neither the progression patterns nor the same anatomical areas are involved or follow a reproducible anatomic sequence, even in series of patients belonging to comparable social and cultural environments. Approximately 25% of AD brains show atypical patterns of structural damage, usually classified as hippocampal sparing and limbic predominant AD (Murray et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer-and Lewyrelated pathologies were immunostained and then analyzed using 3 custom-designed color deconvolution ImageScope algorithms. 13 Antibody information and detailed methods on quantification are available in appendix e-1. All neuropathologic analyses were performed blinded to group status.…”
mentioning
confidence: 99%
“…Despite reasonable interrater agreement when using standardized criteria [84,[103][104][105], no one set of histopathologic criteria for AD has been uniformely accepted by neuropathologists. These algorithms that only considered the classical "plaque and tangle" phenotype of AD did not recognize other subtypes [74,106,107]. Analysis of 1,677 cases with antemortem diagnosis of dementia from the NACCR showed that 82.4% fell into diagnostic "boxes" that are within the consensus recommendations, while the others were "atypical" cases [108].…”
Section: Problems In the Neuropathologic Diagnosis Of Alzheimer's Dismentioning
confidence: 99%
“…While MAPT H1H1 genotype was high (~70 %) in NFTD and LP-AD, and similar to typical AD (59%), tau and Aβ burden in frontal cortex were very low in NFTD, differentiating it from AD subtypes, including LP-AD. Significant pathological differences between NFTD and LP-AD suggest that it may not merely be a variant of AD [106]. Volumetric MRI analysis could reliably track the distribution of NFT pathology and predict pathological subtypes of AD [118].…”
mentioning
confidence: 99%